Legal Protection Against Offenders in the Process of Investigation in the Resort Police of Denpasar City - Dian Martina Octavia; Simon Nahak; I Ketut Widia (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2019)
The involvement of children in a crime is a phenomenon that is rife. As is the case in the Denpasar City Police Department, where there are children who commit sexual intercourse with friends of their age. In the investigation process, the child as the perpetrator of the crime, found a gap between the prevailing norms and practice, namely in Article 64 of Law Number 17 Year 2016 concerning Child Protection stipulates that, special protection for children facing the law, which is wrong one is getting assistance by a parent or guardian. This research was analyze the form of legal protection against the offender's offender in the investigation process and the obstacles to children as perpetrators of criminal acts in the investigation process at the Denpasar City Police Department. This research was empirical research conducted through the method of legislation and legal concepts as the basis of research. The approach in this study uses the legal concept approach, and the legal approach. Based on the results, it was found that the form of child protection as an offender in the police investigation process was divided into two, namely Preventive protection and Repressive protection. Special treatment of children as perpetrators of criminal offenses is carried out with diversion. The diversion effort is one of the Preventive efforts applied to children facing the law which is a settlement of criminal cases outside the court while the Repressive effort that can be done is to provide a quick, precise and efficient investigation process. The factors that become obstacles in the context of investigating children are the factors of underage children, which makes it difficult for the investigation process, the number of parties involved, parents and surrounding communities who are less concerned. The advice given is first, full awareness of the police is needed in the preventive and repressive stages of children facing the law so that in the future this case can be handled properly and efficiently. Second, it is necessary to familiarize parents or related parties who stumble over child problems that intersect with the law so that in the future there will be no more indifference from the parents or related parties in dealing with such crimes.